Analisis gaya belajar dalam konteks diferensiasi pembelajaran menulis - Elis Mulyati; Dian Indihadi; Seni Apriliya (Universitas Sebelas Maret, 2024)
Peserta didik mempunyai gaya belajar yang unik sehingga guru harus merancang pembelajaran yang berbeda. Penelitian ini dilakukan dengan tujuan untuk mendeskripsikan analisis proses dan hasil pembelajaran berbasis gaya belajar dalam konteks diferensiasi pembelajaran menulis. Penelitian ini menggunakan penelitian kualitatif dengan jenis studi kasus. Penelitian studi kasus ini melibatkan seluruh peserta didik kelas IV Sekolah Dasar di 5 Kecamatan di Kota Tasikmalaya dengan jumlah 100 peserta didik. Sampel diambil dengan Teknik purposive sampling. Teknik pengumpulan data berupa wawancara, angket gaya belajar, dan studi dokumentasi. Temuan penelitian mengungkapkan bahwa: (1) pelaksanaan pembelajaran gaya belajar peserta didik dalam konteks diferensiasi pembelajaran menulis di Kelas IV Sekolah Dasar menghasilkan rerata skor yang berkategori baik yang ditandai dengan terpenuhi dan terlaksanakannya proses pembelajaran secara runtut diawali persiapan pembelajaran sampai dengan proses penutupan pembelajaran di kelas; dan (3) penilaian dan hasil pembelajaran gaya belajar peserta didik dalam konteks diferensiasi pembelajaran menulis di Kelas IV Sekolah Dasar menghasilkan rerata skor yang berkategori baik yang ditandai dengan terpenuhinya persiapan penilaian sampai dengan pelaksanaan tindak lanjut terhadap pengetahuan peserta didik. Maka, dapat disimpulkan bahwa pelaksanaan pembelajaran dan penilaian hasil pembelajaran gaya belajar peserta didik dalam konteks diferensiasi pembelajaran menulis di Kelas IV Sekolah Dasar menghasilkan rerata skor yang berkategori baik. Learning style analysis in the context of writing learning differentiation Abstract: Learners have unique learning styles so that teachers must design differentiated learning. This study was conducted with the aim of describing the analysis of learning style-based learning processes and outcomes in the context of writing learning differentiation. This research uses qualitative research with the type of case study. This case study research involved all fourth grade students of elementary schools in 5 sub-districts in Tasikmalaya City with a total of 100 students. The sample was taken with purposive sampling technique. Data collection techniques were interviews, learning style questionnaires, and documentation studies. The research findings revealed that: (1) the implementation of learning styles of learners in the context of differentiation of writing learning in Class IV elementary schools produces an average score that is categorized as good which is characterized by the fulfillment and implementation of the learning process coherently starting from the preparation of learning to the closing process of learning in the classroom; and (3) assessment and learning outcomes of learning styles of learners in the context of differentiation of writing learning in Class IV elementary schools produces an average score that is categorized as good which is characterized by the fulfillment of the preparation of assessment to the implementation of follow-up on the knowledge of learners. So, it can be concluded that the implementation of learning and assessment of learning outcomes of learning styles of learners in the context of differentiation of writing learning in Class IV Elementary School produces an average score that is categorized as good.